2
$\begingroup$

Let $M$ be a $n$-dimensional manifold and let

$$\star : \Lambda^p(M) \longrightarrow \Lambda^{n-p} : \beta \longmapsto \star \beta$$

be the Hodge star operator, such that

$$ ( \alpha, \beta ) \enspace = \enspace \int_M \alpha \wedge \star \beta$$

for all $\alpha \in \Lambda^p$. Here, $\big( \boldsymbol{\cdot}, \boldsymbol{\cdot} \big)$ denotes the inner product, defined as

$$ (\alpha, \beta) \enspace = \enspace \frac{1}{p!} \int_M \alpha_{i_1 \ldots i_p} \; \beta_{j_1 \ldots j_p} \; g^{i_1 j_1} \cdots g^{i_p j_p} \; dV$$

Show that:

$$\star \big( dx^{i_1} \wedge \ldots \wedge dx^{i_p} \big) \enspace = \enspace \frac{\sqrt{\det g}}{(n-p)!} \cdot g^{i_1 j_1} \cdots g^{i_p j_p} \cdot \varepsilon_{j_1 \ldots j_n} \cdot dx^{j_{p+1}} \wedge \ldots \wedge dx^{j_n}$$



${}$

Now, I suppose this is a pretty standard problem, when dealing with differential geometry -- however, I neither managed to solve it myself nor did I find a complete proof of that proposition. Most of the proofs I found were either missing some vital step, or did not bother to expand the proof as detailed as I would need it to understand.

Can anyone help me by providing a source for a proof or can contribute a proof himself? I would really appreciate it.

${}$



${}$

P.S.: I found the answer to How to derive the coordinate expression of the Hodge dual? useful, but I don't understand some of the steps. I copied the proof and marked the steps I don't understand with a Question mark ''?''

Since both sides are linear in $\omega$, it suffices to check on a basis. Let $\omega := \mathrm{d}x^{1}\wedge...\wedge \mathrm{d}x^{k}$. Then, one immediately notices that $\eta \overset{?}{=} \varepsilon^{i_1 ... i_k} \omega$. Observe that \begin{align*} ⟨\omega,\eta⟩ \ vol \enspace &= \enspace \varepsilon^{i_1 ... i_k} \ ⟨\omega,\omega⟩ \sqrt{g} \ \mathrm{d} x^1 \wedge ... \wedge \mathrm{d}x^n\\ &\overset{?}{=} \enspace \sqrt{g} \ \varepsilon^{i_1 ... i_k} \ g^{1 j_1} ... g^{k j_k} \ \varepsilon_{j_1 ... j_k} \mathrm{d} x^1 \wedge ... \wedge \mathrm{d}x^n\\ &= \enspace \sqrt{g} \ \varepsilon^{i_1 ... i_k} \ \mathrm{d} x^1 \wedge ... \wedge \mathrm{d}x^n\\ &= \enspace \sqrt{g} \ \Big( \frac{1}{(n-k)!} g^{i_1 j_1} ... g^{i_k j_k} \ \varepsilon_{j_1 ... j_n} \ \varepsilon^{j_{k+1} ... j_n} \Big) \ \mathrm{d} x^1 \wedge ... \wedge \mathrm{d}x^n\\ &\overset{?}{=} \enspace \mathrm{d} x^1 \wedge ... \wedge \mathrm{d} x^k \wedge \Big( \frac{\sqrt{g}}{(n-k)!} g^{i_1 j_1} ... g^{i_k j_k} \ \varepsilon_{j_1 ... j_n} \Big) \ \mathrm{d} x^{j_{k+1}} \wedge ... \wedge \mathrm{d}x^{j_n}\\ &= \enspace \omega \wedge \widetilde{\eta} \end{align*}

$\endgroup$
0
$\begingroup$

I now figured out something, but I am not sure whether my calculations are correct, so please tell me if my approach is acceptable.

Let $\alpha \in \Lambda^p$ such that $\alpha = \frac{1}{p!} \; \alpha_{k_1 \ldots k_p} \; dx^{k_1} \wedge \ldots dx^{k_p}$ and let $\beta = dx^{j_1} \wedge \ldots \wedge dx^{j_p}$. Then by assumption

\begin{align} \alpha \wedge \star \beta \enspace &= \enspace \frac{\sqrt{\det g}}{(n-p)!} \; g^{i_1 j_1} \cdots g^{i_p j_p} \; \varepsilon_{j_1 \ldots j_n} \; \alpha \wedge\Big(dx^{j_{p+1}} \wedge \ldots \wedge dx^{j_n} \Big) \\ &= \enspace \frac{\sqrt{\det g}}{p! \, (n-p)!} \; g^{i_1 j_1} \cdots g^{i_p j_p} \; \varepsilon_{j_1 \ldots j_n} \; \alpha_{k_1 \ldots k_p} \; \Big(dx^{k_1} \wedge \ldots \wedge dx^{k_p} \Big) \wedge \Big(dx^{j_{p+1}} \wedge \ldots \wedge dx^{j_n} \Big) \end{align}

By renaming the indices, one obtains

\begin{align} \alpha \wedge \star \beta \enspace &= \enspace \frac{\sqrt{\det g}}{p! \,(n-p)!} \; g^{i_1 j_1} \cdots g^{i_p j_p} \; \varepsilon_{j_1 \ldots j_p k_{p+1} \ldots k_n} \; \alpha_{k_1 \ldots k_p} \; \underbrace{\Big(dx^{k_1} \wedge \ldots \wedge dx^{k_p} \Big) \wedge\Big(dx^{k_{p+1}} \wedge \ldots \wedge dx^{k_n} \Big)}_{= \; \varepsilon^{k_1 \ldots k_n} \; dx^1 \wedge \ldots \wedge dx^n} \\ &= \enspace \frac{\sqrt{\det g}}{p! \, (n-p)!} \; g^{i_1 j_1} \cdots g^{i_p j_p} \; \varepsilon_{j_1 \ldots j_p k_{p+1} \ldots k_n} \; \alpha_{k_1 \ldots k_p} \; \; \varepsilon^{k_1 \ldots k_n} \; \Big( dx^1 \wedge \ldots \wedge dx^n \Big) \end{align}

Using $dV =\sqrt{\det g} \cdot dx^1 \wedge \ldots \wedge dx^n$, one gets

\begin{align} \alpha \wedge \star \beta \enspace &= \enspace \frac{dV}{p! \,(n-p)!} \; g^{i_1 j_1} \cdots g^{i_p j_p} \; \varepsilon_{j_1 \ldots j_p k_{p+1} \ldots k_n} \; \varepsilon^{k_1 \ldots k_n} \; \alpha_{k_1 \ldots k_p}\\ &= \enspace \frac{dV}{p! \,(n-p)!} \; g^{i_1 j_1} \cdots g^{i_p j_p} \; (n-p)! \; \delta^{k_1 \ldots k_p}_{j_1 \ldots j_p} \; \alpha_{k_1 \ldots k_p} \\ &= \enspace \frac{dV}{p!} \; g^{i_1 j_1} \cdots g^{i_p j_p} \; p! \; \alpha_{[j_1 \ldots j_p]} \\ &= \enspace dV \; g^{i_1 j_1} \cdots g^{i_p j_p} \; \alpha_{j_1 \ldots j_p} \end{align}

which coincides with the inner product. Here, the antiymmetry of $\alpha$ was used. Note that the factor of $\tfrac{1}{p!}$ within the inner product arises from a $p$-form $\gamma = \tfrac{1}{p!} \, \gamma_{m_1 \ldots m_p} \, dx^{m_1} \wedge \ldots \wedge dx^{m_p}$ being inserted into the inner product, i.e. $(\alpha, \gamma)$.

Please tell me what you think.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.